(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
At a time when the complexity of worldviews and the diversity of needs are increasing given the stability and instability that exists throughout the world today, every student should understand globalization, ecological, social and economic processes and the events in our lives understand correctly in order to draw the correct conclusions with a scientific attitude, he should first have a certain level of theoretical thinking. Such an ability arises from the study of universal, philosophical ideas when the opposite happens, that is, the neglect and denial of the universal aspects of science leads to a slowdown in the development of society. Science as a complex social phenomenon is a special direction of human activity.